Evaluation Analysis of Small Capacity Rooftop Solar Electricity (PLTS) Development Plans at PT Pertamina Gas - Ardianto, Kurniawan; Windarta, Jaka; Wardaya, Asep Yoyo (Riviera Publishing, 2024)
Solar Power Plant (PLTS) is one type of new and renewable energy (EBT) generated from the Sun. Indonesia is a country that has considerable solar energy development potential of 4.8 Kw h/m2, but currently its utilization is still very low at only 0.01%. This study aims to evaluate the development plan of small-capacity rooftop solar power plants at oil and gas facilities owned by PT Pertamina Gas (Pertagas). This study uses PVSyst and Helioscope software to analyze the potential and efficiency of rooftop solar power plants. The results show that the planned installation of small-capacity rooftop solar power plants (±0.15 kW) in several Pertagas operational areas can support electricity supply for oil and gas distribution in Indonesia. The utilization of solar energy, which is one of the new renewable energy (EBT), is expected to increase the national energy mix in accordance with the government's target. This research provides evaluation and recommendations for the development of rooftop solar power plants at oil and gas facilities to support national energy independence and security.